Can schools teach citizenship?. Issue 1 (2nd January 2020) - Merry, Michael S.
ABSTRACT: In this essay I question the liberal faith in the efficacy and morality of citizenship education (CE) as it has been traditionally (and is still) practiced in most public state schools. In challenging institutionalized faith in CE, I also challenge liberal understandings of what it means to be a citizen, and how the social and political world of citizens is constituted. I interrogate CE as defended in the liberal tradition, with particular attention to Gutmann's 'conscious social reproduction'. I argue that CE in practice does not operate on the bases of non-repression or non-discrimination, and has weak claims for legitimacy. In fact, CE in many forms reproduces social inequalities, and contributes to the expulsion of disadvantaged students from schools and from the ranks of recognized citizens.